Determination of Land Use and Land Cover by Machine Learning Methods Using Satellite Images - Oturanç, Sevim Yasemin (Fırat University, 2025)
With the development of satellite techniques, remote sensing techniques are used more frequently in remote sensing studies to determine land use and land cover. Nergizlik Reservoir is an important water source and since residential areas, agricultural lands and forest areas are located around it, regular observation of the land cover is necessary. The main purpose of this study is to determine land use and land cover around Nergizlik Reservoir by pixel-based image classification methods, band ratio techniques and to compare the general accuracy of these techniques and to determine the most appropriate method for the field of study. In this study, Sentinel-2B satellite image of Nergizlik Reservoir taken on January 3, 2024 was used. The image was classified by Support Vector Machines (SVM) and Artificial Neural Networks (ANN) pixel-based classification method using red, blue and green bands. Normalized Difference Vegetation Index (NDVI) and Normalized Difference Red Edge Index (NDRE) band ratio techniques were applied to the image. Land use and land cover maps were created. SVM provided 89% accuracy, ANN 88%, NDVI 81%, NDRE 84%. All methods provided the expected accuracy and the pixel-based SVM classification method provided higher accuracy than other methods.

Uydu teknolojilerinin gelişmesiyle birlikte, arazi kullanımı ve arazi örtüsü belirlemek amacıyla uzaktan algılama teknikleri daha sık kullanılmaktadır. Nergizlik barajı önemli bir su kaynağı olup, çevresinde yerleşim alanları, tarım arazileri ve orman alanları bir arada bulunduğu için arazi örtüsünün düzenli olarak gözlemlenmesi gereklidir. Bu çalışmanın temel amacı Nergizlik Baraj Gölü çevresinde piksel tabanlı görüntü sınıflandırma yöntemleri ile sınıflama işlemi uygulayarak ve bant oranlama teknikleri kullanarak arazi kullanım ve arazi örtüsünü belirlemek, bu tekniklerin genel doğruluklarını karşılaştırmak ve çalışma alanına en uygun yöntemi tespit etmektir. Bu çalışmada Nergizlik Baraj Gölü’nün 3 Ocak 2024 tarihinde alınan Sentinel-2B uydu görüntüsü kullanılmıştır. Görüntü, kırmızı, mavi ve yeşil bantları kullanılarak, Support Vector Machines (SVM), Artificial Neural Networks (ANN) yöntemiyle piksel tabanlı sınıflandırma yöntemiyle sınıflandırılmıştır. Görüntüye Normalized Difference Vegetation Index (NDVI), Normalized Difference Red Edge Index (NDRE) bant oranlama teknikleri de uygulanmıştır. Arazi kullanımı ve arazi örtüsü haritaları oluşturulmuştur. Bu çalışmada SVM %89, ANN %88, NDVI %81, NDRE %84 doğruluk sağlamıştır. Tüm yöntemler beklenen doğruluğu sağlamış olup, piksel tabanlı SVM sınıflama yönteminin diğer yöntemlere göre daha yüksek doğruluk sağladığı tespit edilmiştir.
Uydu Görüntüleri Kullanarak Makine Öğrenme Yöntemleri ile Arazi Kullanımı ve Arazi Örtüsünün Belirlenmesi
Keywords: Environmentally Sustainable Engineering; Çevresel Olarak Sürdürülebilir Mühendislik; Photogrammetry and Remote Sensing; Fotogrametri ve Uzaktan Algılama